Testing the durability of copper based preservative treated bamboos in ground-contact for six years - Tomak, Eylem D.; Topaloglu, Elif; Ermeydan, Mahmut A.; Pesman, Emrah (Springer, 2022)
In this study, durability of bamboo samples in terms of the variability of location along culm height (top, middle and bottom) were evaluated in a ground-contact field test for six years in comparison to Scots pine and beech wood samples. Bamboo and wood samples were treated with Wolmanit-CB (CCB) and Tanalith-E (Tan-E) solutions, and then were installed in a field located in the North-West of Turkey. The decay resistance of samples was assessed by weight loss, and compared by SEM observations and FTIR analysis. Furthermore, chemical leaching from the samples was detected by ICP-OES after the test. Results showed that un-treated bamboo and wood samples had a very low durability such that weight losses were found as 64-80% for bamboo and 57-63% for wood samples. The SEM micrographs showed the characteristics decay patterns of soft-rot type I and brown-rot fungi in the parenchyma cells, vessels and fibers in vascular bundles. Fungal hyphae within the cell walls resulted in the gradual breakdown of the cell wall layers. FTIR analysis revealed the mechanism of the biodegradation, which indicates the reduction of carbohydrate content. The weight loss in CCB and Tan-E treated bamboo samples was reduced as 20-45% depending on bamboo height parts, but the wood preservatives did not ensure sufficient resistance for six years against soil degrading organisms since more than half of the chemical amount leached out from the bamboos to soil. Weight losses were well confirmed by chemical leaching rates for both CCB and Tan-E. It was observed that the lower parts of the culm were more durable, which was also in accordance with ICP-OES and SEM analysis. Copper-based preservatives seemed to be more efficient in pine and beech wood samples than bamboos since the impregnability of bamboo was much lower than that of wood.
Keywords: Ground-contact; Bamboo; Copper-based preservatives; Decay; Leaching